Дослідження процесу додаткового очищення питної води методом поверхневого плазмонного резонансу - Радов, Денис Георгійович; Маслов, Володимир Петрович; Дорожинський, Гліб Вячеславович (НТУ "ХПІ", 2016)
Вперше досліджено процес очищення вимороженої водопровідної води методом на основі поверхневого плазмонного резонансу. Оцінено ефективність кількаразового заморожування та введено коефіцієнт виморожуваності – критерій, що визначає сприятливість води певного типу до очищення від домішок виморожуванням. Запропоновано параметри для оцінки ефективності очищення води. Результати досліджень можуть бути використані для вдосконалення існуючих та створення нових методик контролю процесу очищення водопровідної води.

For the first time the control for water purification process by developed method based on the phenomenon of surface plasmon resonance (SPR) was performed. It is shown that the development of alternative control method of purification of water based on the phenomenon of SPR is advanced direction which allows rapid analysis and can be less expensive than existing methods, has high sensitivity to low concentrations of analytes and high accuracy. For the first time a was study the effectiveness of cleaning water samples by rapid method using specialized equipment "Aqua-polaritons". Was proposed to apply the following parameters for water purification efficiency: a) the value of the number of cycles freezing – k; b) saturation point clickthrough water – KEOk; c) the maximum derivative KEO – maxKEO; d) ratio of freezing – KV. The research results can be used to improve existing and create new methods of process quality control of water purification.
Investigation of further purification of drinking water by surface plasmon resonance
Keywords: водопровідна вода; очищення води; виморожування; поверхневий плазмонний резонанс; tap water; water purification; freezing; surface plasmon resonance